Codetermination for the sustainable company - Norbert Kluge; Sigurt Vitols (Hans-Böckler-Stiftung, Institut für Mitbestimmung und Unternehmensführung (I.M.U.), 2020)
The 'Green Deal' will be a civic achievement only when workers are able to participate in it actively. Codetermination as a guiding principle for sustainable companies sets the course for decent work, incomes, production locations and, at the same time, for competitiveness and a healthy environment. Research has provided strong evidence of the efficiency and functionality of codetermination. However, there must be political will and support for it. It is the democratic design principle of the social market economy.
Keywords: 330; Codetermination; green deal